RANCANG BANGUN ALAT PENJERNIH AIR PORTABLE UNTUK PERSEDIAAN AIR DI KOTA DUMAI - Rizqi Ilmal Yaqin; Boby Wisely Ziliwu; Bobby Demeianto; Juniawan Preston Siahaan; Yuniar Endri Priharanto; Iskandar Musa (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2020)
Dumai City has poor quality water availability. The resulting water has poor physical and chemical conditions. Poor water quality due to the effects of industrial and home industrial waste. The decline in water quality causes the survival of living things to be disrupted. The use of water itself is used for aquaculture. Aquaculture water must have a quality that meets the standards. Therefore, water quality must be considered in aquaculture. The purpose of this study is to determine the reliability of the filter in a water filter. Water filter materials used are natural zeolite stone, silica sand, greensand sand, activated carbon, Bio-ball and cotton filter. Portable cylindrical filter device with a diameter of 25mm and length of 254mm. outdoor water quality portable water filter is tested with the acidity or pH meter, Total Dissolve Solid or the level of water clarity, Salinity, and discharge of water from the portable water filter. Discharge of water entering the portable water purifier is 0.22 Liters / second to 0.28 Liters / Second. Discharge of water that comes out is 0.13 Liters / Second to 0.16 Liters / Second. Changes in water quality can be seen from TDS, from 178ppm to 359ppm. Water quality can be seen from the pH of 8.48 mg / L to 7.95 mg / L and for Salinity from 1% to 0%. Portable water purifier can improve water quality in the city of Dumai. But in the future there should be further research on the quality of water produced from portable water purifiers.